Library Management at the Aceh Office of Library and Archive - Niswanto, Niswanto; Naimah, Cut; AR, Murniati (FKIP Universitas Lampung, 2020)
Library Management at the Aceh Office of Library and Archive. Objectives: The objective of this study is to know about library management in procurement, implementation and evaluation program of library collection. Methods: The approach of this study is qualitative approach. The subject of this study is head of library division, a librarian and library user. The data collection techniques are classified from observation, interview and documentation. Findings: The result of this study indicates that collection procurement program is conducted every five years and annually based on survey of library users needs and then collaborates between institutions, publishers and by purchasing through state expenditure and Aceh expenditure income budget. The implementation of library collection through a collection development by selecting books and forming a selection team to determine which books are allowed to be held in library. The collection maintenance and preservation are carried based on the applicable stages including: fumigation, binding, restoration, preservation, conservation, lamination, and weeding. The head of department and head of division evaluate the program at the end of the year.Keywords: Library management, library and archive office, IndonesiaDOI: 10.23960/jpp.v10.i2.202005